1997
DOI: 10.1111/j.1469-7610.1997.tb01599.x
|View full text |Cite
|
Sign up to set email alerts
|

Another Advanced Test of Theory of Mind: Evidence from Very High Functioning Adults with Autism or Asperger Syndrome

Abstract: Previous studies have found a subgroup of people with autism or Asperger Syndrome who pass second-order tests of theory of mind. However, such tests have a ceiling in developmental terms corresponding to a mental age of about 6 years. It is therefore impossible to say if such individuals are intact or impaired in their theory of mind skills. We report the performance of very high functioning adults with autism or Asperger Syndrome on an adult test of theory of mind ability. The task involved inferring the ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
962
5
32

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,558 publications
(1,047 citation statements)
references
References 35 publications
28
962
5
32
Order By: Relevance
“…The second baseline condition consisted of an odd-even number judgment task. This second baseline was included because it has been shown that 1 The current dataset only included women, as there is evidence that AM (Andreano & Cahill, 2009), and possibly ToM (Baron-Cohen et al, 1997), differ across sex. Although beyond the scope of the current study, sex differences in brain networks underlying AM and ToM is an important topic for future research.…”
Section: Stimulimentioning
confidence: 99%
“…The second baseline condition consisted of an odd-even number judgment task. This second baseline was included because it has been shown that 1 The current dataset only included women, as there is evidence that AM (Andreano & Cahill, 2009), and possibly ToM (Baron-Cohen et al, 1997), differ across sex. Although beyond the scope of the current study, sex differences in brain networks underlying AM and ToM is an important topic for future research.…”
Section: Stimulimentioning
confidence: 99%
“…Prefrontal regions are mainly related to the social-cognitive aspect of mentalizing, while the amygdala und superior temporal cortex are linked to the social-perceptual aspect (Tager-Flusberg and Sullivan, 2000). However, it can be assumed that the Eyes test used in our study is a measure of both the perceptual and the cognitive component of mentalizing through the attribution of complex mental states (Baron-Cohen et al, 1997, Baron-Cohen, et al, 2001, Shur et al, 2008. In line with this claim, two neuroimaging studies have shown the activation of temporal regions, prefrontal cortex, medial frontal lobe and the amygdala during test performance, confirming that both aspects of mentalizing are involved (Baron-Cohen et al, 1999, Russell et al, 2000.…”
mentioning
confidence: 99%
“…For example, the eyes are used to modulate social interactions by indicating turn-taking during conversations and to communicate social dominance and appeasement (Exline 1971;Kendon 1967). The eyes also provide rich information about the emotional state of another (Baron-Cohen et al 1997).…”
mentioning
confidence: 99%